The Effect of the Administration of Calcium Chloride (CaCl2) and Phosphoric Acid Fertilizer (H3PO4) on the Growth and Production of Strawberry (Fragaria ananassa) - Rasyid, Harun; Zakia, Aulia; Triyuana, Resty Mirza (Universitas Muhammadiyah Malang, 2021)
Strawberry production in Indonesia has been on the rise in various regions, including Aceh, Riau, Jambi, DKI Jakarta, West Java, Central Java, East Java, and others. According to the Central Bureau of Statistics (2021), production fluctuated from 573.00 tons in 2019 to 559.00 tons in 2020, rebounding to 838.00 tons in 2021. Factors influencing production include land availability, proper fertilization methods, and planting media. Adequate fertilization, considering both dosage and frequency, plays a crucial role. The study, conducted at Balitjestro GreenHouse in Batu City, East Java, focused on the interaction between lime and fertilizer on strawberry plant growth and yield. Synthetic fertilizers, particularly phosphate fertilizers, are essential for plant growth. The research utilized a completely randomized design with two factors: CaCl2 lime (S) and phosphoric acid fertilizer (R), resulting in two treatment combinations (4x4). Each treatment, repeated three times, yielded 48 experimental units, with one plant per unit. Results indicated that the addition of CaCl2 lime and phosphoric acid fertilizer had a minimal impact on strawberry plant growth and production. Specific combinations, such as calcium chloride and phosphoric acid fertilizer with KCL 7.2 grams and urea 12.5 grams, did not significantly affect vegetative growth parameters like plant height and leaf count. However, these combinations did influence strawberry plant production. The study underscores the need for careful nutrient management to optimize strawberry production in Indonesia.